Trade-Induced Inefficiency in ASEAN Agriculture: A Stochastic Frontier Analysis of Technical and Environmental Efficiency - Daffa Ibra Danendra; Tanti Novianti; Nia Kurniawati Hidayat (Jurnal Manajemen dan Agribisnis, 2026)
Background: Agricultural systems in ASEAN face increasing pressure from rising food demand; however, prior studies predominantly assess technical efficiency without jointly considering environmental performance and trade-related inefficiency.Purpose: This study evaluates technical and environmental efficiency in ASEAN agriculture and examines how trade dynamics influence this inefficiency.Design/methodology/approach: A panel dataset covering ASEAN countries from 2003 to 2022 is analyzed using stochastic frontier analysis with a translog production function and time-varying inefficiency effects.Findings/Result: The findings indicate that output growth is driven more by efficiency improvements and policy support than by input expansion. Capital contributes significantly to production, whereas land, labor, and fertilizer exhibit diminishing effectiveness. The average technical efficiency reaches 0.68, whereas environmental efficiency remains lower at 0.46, suggesting a persistent sustainability gap. In addition, net export expansion is associated with higher inefficiency when domestic capacity becomes insufficient.Conclusion: Enhancing efficiency, technological upgrading, and environmental sustainability while aligning trade expansion with domestic capacity is essential for long-term agricultural performance.Originality/value (State of the art): This study provides an integrated empirical assessment linking technical efficiency, environmental performance, and trade-related inefficiency in ASEAN agriculture, offering evidence of the alignment of trade expansion with sustainable productivity strategies. Keywords: environmental efficiency, technical efficiency, trade efficiency, translog, time-varying